Investigation of myocardial dysfunction using three-dimensional speckle tracking echocardiography in a genetic positive hypertrophic cardiomyopathy Chinese family. (6th July 2018) - Wang, Jing; Guo, Rui-Qi; Guo, Jian-Ying; Zuo, Lei; Lei, Chang-Hui; Shao, Hong; Wang, Li-Feng; Zhang, Yan-Min; Liu, Li-Wen
Abstract: Background: We previously reported four heterozygous missense mutations of MYH7, KCNQ1, MYLK2, and TMEM70 in a single three-generation Chinese family with dual Long QT and hypertrophic cardiomyopathy phenotypes for the first time. However, the clinical course among the family members was various, and the potential myocardial dysfunction has not been investigated. Objectives: The objective of this study was to investigate the echocardiographic and electrocardiographic characteristics in a genetic positive Chinese family with hypertrophic cardiomyopathy and further to explore the association between myocardial dysfunction and electric activity, and the identified mutations. Methods: A comprehensive echocardiogram – standard two-dimensional Doppler echocardiography and three-dimensional speckle tracking echocardiography – and electrocardiogram were obtained for members in this family. Results: As previously reported, four missense mutations – MYH7 -H1717Q, KCNQ1 -R190W, MYLK2 -K324E, and TMEM70 -I147T – were identified in this family. The MYH7 -H1717Q mutation carriers had significantly increased left ventricular mass indices, elevated E/e' ratio, deteriorated global longitudinal stain, but enhanced global circumferential and radial strain compared with those in non-mutation patients (all p<0.05). The KCNQ1 -R190W carriers showed significantly prolonged QTc intervals, and the MYLK2 -K324E mutation carriers showed inverted T-waves (both p<0.05). However, the TMEM70 -I147T mutation carriers had similar echocardiography and electrocardiographic data as non-mutation patients. Conclusions: Three of the identified four mutations had potential pathogenic effects in this family: MYH7 -H1717Q was associated with increased left ventricular thickness, elevated left ventricular filling pressure, and altered myocardial deformation; KCNQ1 -R190W and MYLK2 -K324E mutations were correlated with electrocardiographic abnormalities reflected in long QT phenotype and inverted T-waves, respectively.